Perancangan Sistem Bot Alert Telegram Sebagai Notifikasi Deteksi Serangan Ping of Death Berbasis Snort - Rachman Juliandi, Dicky; Karman, Joni; Rusdiyanto (STMIK Budi Darma, 2024)
The Ping of Death attack is a type of denial of service (DoS) attack that exploits a vulnerability in the Internet Control Message Protocol (ICMP). This attack is carried out by sending a large number of pings that exceed the maximum limit allowed by the network, causing the server or network device to become slow or even unresponsive. This attack can have a severe impact on server and network performance, especially for services that require high availability such as the Sinanan Lubuklinggau server. This research aims to design a Telegram Bot alert system as an automatic notification tool to detect Ping of Death attacks on the Sinanan Lubuklinggau server, using Snort, a detection system software that is infiltrating the